Efeito da glicerina na eficiência de colchões lavadores microemulsionados a base de óleo vegetal - Araújo, Elayne Andrade (2019)
Flushing/spacers are cleanup fluids, pumped ahead of the cement paste, with the purpose displacing and removing the drilling fluids and, still, reversing the wettability of the walls the rock formation. The flushing fluids need to be compatible with the cement and the drilling fluid because they can cause a mixture with excessive viscosity able to decrease the efficiency of displacement of the drilling fluid and, consequently, to render the adhesion of the cement weak. Therefore, the objective of this work was to develop microemulsion-based flushing fluids and to analyze the influence of glycerin on the removal of the drilling fluid, wettability inversion compatibility between the flushing/drilling fluid, flushing/cement and drilling fluid/ flushing/cement paste and in the compressive strength of the cement matrix. For this, three diagrams of ternary phases were developed, with the following components: vegetable oil, as oil phase (FO); tween 80, as non-ionic surfactant (T); and glycerin, glycerin/water (1:1) and water, as aqueous phases. Then, a sample of each diagram with the same composition was chosen, being 35% FO, 55% T, 5% FA. The microemulsions (ME) of type water in oil W/O were analyzed by thermal stability, which showed that the presence of glycerin does not change physics aspects (homogeneity) the system under high temperatures. In non-aqueous drilling fluid removal tests, the microemulsions systems, pure and diluted, exhibited removal efficiency of, approximately, 100%. In the tests of wettability inversion of the of W/O to O/W, only the diluted systems were able to invert. In the compatibility of the diluted microemulsions fluids, drilling fluid and cement slurry, it was verified that the mixtures were compatible, and no signs of incompatibility such as phase separation, variations of viscosity, gelation and flocculation were observed. Though, the presence of glycerin in these systems decreased the viscosity of the blends. The contamination of the cement paste with the diluted flushing fluids, in the proportion 90/10 (v/v) respectively, showed that there was decrease in the cement strength, however, the diluted glycerin/water system presented better hydration of the cement paste, confirmed by X-ray diffraction (XRD) analysis, which showed that glycerin, at high concentrations, directly influence the properties of the hydrated cement.